2010
DOI: 10.1111/j.1476-5381.2010.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of 2‐arachidonoyl glycerol in the increased consumption of and preference for ethanol of mice treated with neurotoxic doses of methamphetamine

Abstract: Background and purpose: Methamphetamine (METH) is a psychostimulant amphetamine that causes long-term dopaminergic neurotoxicity in mice. Hypodopaminergic states have been demonstrated to increase voluntary ethanol (EtOH) consumption and preference. In addition, the endocannabinoid system has been demonstrated to modulate EtOH drinking behaviour. Thus, we investigated EtOH consumption in METH-lesioned animals and the role of cannabinoid (CB) signalling in this EtOH drinking. Experimental approach: Mice were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…In other investigations, the self‐administration of alcohol was demonstrated to increase the extracellular level of 2‐AG in the NAc, which is linked to the amount of alcohol consumed, but not of AEA in the same region (Caille, Alvarez‐Jaimes, Polis, Stouffer, & Parsons, ). Furthermore, a mouse model of methamphetamine‐induced neurotoxic lesioning of nigrostriatal dopaminergic projections exhibited increased alcohol intake and enhanced 2‐AG levels in the limbic forebrain tissues comprising the anterior cingulate and the NAc (Gutierrez‐Lopez et al, ). The pharmacological blockade of MAGL also enhanced alcohol consumption and preference (Serrano et al, ; Figure ).…”
Section: The Role Of the Ecb System In Alcohol Intake/self‐administramentioning
confidence: 99%
“…In other investigations, the self‐administration of alcohol was demonstrated to increase the extracellular level of 2‐AG in the NAc, which is linked to the amount of alcohol consumed, but not of AEA in the same region (Caille, Alvarez‐Jaimes, Polis, Stouffer, & Parsons, ). Furthermore, a mouse model of methamphetamine‐induced neurotoxic lesioning of nigrostriatal dopaminergic projections exhibited increased alcohol intake and enhanced 2‐AG levels in the limbic forebrain tissues comprising the anterior cingulate and the NAc (Gutierrez‐Lopez et al, ). The pharmacological blockade of MAGL also enhanced alcohol consumption and preference (Serrano et al, ; Figure ).…”
Section: The Role Of the Ecb System In Alcohol Intake/self‐administramentioning
confidence: 99%
“…Notably, self-administration of ethanol increases interstitial levels of 2-AG in the NAc that are correlated with the amount of ethanol consumed, but does not alter levels of AEA in this brain region (Caillé et al, 2007). Additionally, a methamphetamine-induced neurotoxic lesion of nigrostriatal dopaminergic projections (Granado et al, 2010; Sanchez et al, 2003) is associated with increased levels of ethanol consumption and preference, and this mouse model of enhanced ethanol intake displays increased tissue concentrations of 2-AG in limbic forebrain sections containing anterior cingulate and NAc (Gutierrez-Lopez et al, 2010). Furthermore, these investigators found that enhanced ethanol consumption and preference were also observed in intact mice treated with the MAGL inhibitor N- arachidonyl maleimide.…”
Section: Ethanol and The Ec Systemmentioning
confidence: 99%
“…Although both anandamide and 2‐AG function as reinforcers in their own right when tested in squirrel monkeys (Justinova et al,2005; Justinova et al,2011), a growing body of evidence suggests that these molecules may exert opposing effects during particular circumstances of reward‐directed behavior. Augmenting 2‐AG levels increases dopamine neurotransmission (Oleson et al,2012) and facilitates reward‐directed behavior (Gutierrez‐Lopez et al,2010; Oleson et al,2012; Wakley and Rasmussen,2009). By contrast, augmenting anandamide levels reduces the potency of cues to motivate reward‐directed behavior.…”
Section: Discussionmentioning
confidence: 99%